Comparison of Loss Characteristics of Coaxial Magnetic Gear According to Three Types - Lee, Jeong-In; Shin, Kyung-Hun; Bang, Tae-Kyoung; Choi, Jang-Young; Kim, Kyong-Hwan; Hong, Keyyong (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, there has been a problem of instability in rare earth prices worldwide. Due to these problems, various structures are being studied to minimize the use of permanent magnets.Methods/Statistical analysis: In this paper, we analyze the loss characteristics of three different types of coaxial magnetic gear (CMG)s using two - dimensional finite element analysis.Findings: This paper, 3 types of CMGs have been analyzed by using the 2-D FEA. The shapes used for the analysis are three types: Surface mounted coaxial magnetic gear (SMCMG), Consequent pole coaxial magnetic gear (CPCMG) and Reluctance coaxial magnetic gear (RCMG).The three types of gear ratios are all seven. For CPCMG and RCMG, the maximum torque is reduced as compared to SMCMG as the permanent magnet usage decreases. However, in case of loss, CPCMG is advantageous for PMloss and RCMG is for coreloss. The efficiency of SMCMG is advantageous, although the three types do not have much difference.Improvements/Applications: Through the two - dimensional finite element analysis, the results of analysis of the losses occurring in three types of magnetic gears were obtained.Â Â